Age at first birth, age at menopause, and risk of ovarian cyst: a two-sample Mendelian randomization study - Su, Qian; Yang, Zhiyong (Frontiers in Endocrinology, 2024)
Background: Increasing observational researches have indicated that hormonal reproductive factors were associated with the ovarian cyst, a common gynecological disease. A two-sample Mendelian randomization (MR) was carried out by investigating the causality of reproductive factors including-age at first birth (AFB), age at natural menopause (ANM) and age at menarche (AAM) and the risk of ovarian cyst (OC).Method: Summary statistics was collected from a large genome-wide association study (GWAS), and we used a two-sample Mendelian randomization study to clarify the causal association between the exposure of AFB(N=542,901), ANM(N=69,360) and AAM(N=29346) and the outcome of the OC (Ncase=20750, Ncontrol=107564). We separately selected 51, 35, 6 single nucleotide polymorphisms (SNPs) as instrumental variables (IVs) for assaying the influence of AFB, ANM and AAM on OC, respectively. Then, the causal relationship was tested through multiply approaches including an inverse-variance weighted method, an MR-Egger regression and a